Actividades lúdicas para estimular la motricidad fina en los niños de 3 a 4 años de Educación Inicial. - Tipanguano García, Natalia Fernanda (2023)
The present investigation with the theme: Playful activities to stimulate fine motor skills in children from 3 to 4 years of Initial Education, which aims to develop a guide of playful activities to stimulate fine motor skills in children from 3 to 4 years of age. Initial Education of the Educational Unit of the Millennium "Jorge Rodríguez Román", in this investigation an interpretive paradigm with a qualitative approach was used that focuses mainly on the perceptions, beliefs, value judgments, opinions and attitudes of the participants, who are involved within the field of study, using the action-research method that seeks to provide an efficient and viable solution to solve the study problem, it is also worth mentioning that interviews, focus groups and direct observation were applied to collect information, parameters that determined the elaboration and application of a guide of recreational activities to solve the problem that was evidenced, which obtained positive results in motor development, which constitutes an essential and enriching factor in the integral development of students, allowing them to acquire skills and abilities.